Arbiter testimony: “Arbitrate what to narrate”. An analysis in the work I Was a Child of Holocaust Survivors by Bernice Einsenstein. - SILVA, Maria Elinaria Rodrigues da (2023)
This paper seeks to analyze the work I Was a Child of Holocaust Survivors by Bernice Eisenstein (2006), through the lens of Arbiter Testimony. The work deals with the author's relationship with her parents, in which she tries to understand her own life and the ghost of the Holocaust that is ever-present in her daily life. This research aims to investigate how the Arbiter Testimony is presented in the work, a concept addressed by Sarmento-Pantoja (2019), given that the arbiter of testimony is given by the one who has heard and arbitrates on what and how to narrate, and may or may not have experienced the boundary event. We will benefit from the critical fortune of Vilela (2012), who discusses the importance of memory, Gagnebin (2009), who discusses the importance of keeping memory alive through narrations, and Sarmento-Pantoja (2019), who argues about the three types of testimonies, the Testis, the Superstes, and the Arbiter. This study is the result of the guidance received in the scientific initiation project Configurações de Resistência em Narrativas Anglófonas Contemporâneas - CRENAC, in which I acted as a FAPESPA (Fundação Amazônia de Amparo a Estudos e Pesquisas) fellow - the project is coordinated by Profa.Dra. Ana Lilia Carvalho Rocha.